Närhet som grepp: Det metonymiska i Tor Ulvens poesi - Edgren, Svala (Tidskrift för litteraturvetenskap, 2024)
Contiguity as Device: The Metonymical in Tor Ulven’s Poetry This article localizes the metonymical elements in Tor Ulven’s poetry. In his essays, Ulven expresses an awareness of the limitations of metaphor in representation. Yet, the poetic consequences of this metaphor skepticism have gained little attention. Through an analysis of some frequent motifs in Ulven’ poetry, the article investigates how Ulven makes use of contiguity, rather than similarity, as a principal poetic device. It also argues that his particular use of the word “som” (like/that) does not primarily function as a way of creating relations of similarity, but rather as a relative pronoun, where “som” activates the subordinate clause by introducing a verb. The purpose of the article is to shed light on the correspondences related to contiguity that permeate Ulven’s poetry and that, it is argued, are central to his poetic imagery.